ISOLASI BAKTERI ASAM LAKTAT DARI KIMCHI DAN KEMAMPUANNYA MENGHASILKAN ZAT ANTI BAKTERI - Benedicta Yolanda Khristnaviera; Vincentia Irene Meitiniarti (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
South Korea is famous for its fermented food called Kimchi, a traditional Korean food fermented from pickled vegetables with a mixture of spicy seasoning. Kimchi is now one of functional food products because of there are lactic acid bacteria that are probiotic and can produce bacteriocin compounds. These bacteriocin compounds may inhibit or have anti-bacterial activity. The purpose of this study was to obtain isolates of lactic acid bacteria from store-bought kimchi and homemade kimchi, to examine the antibacterial agent produced by lactic acid bacteria isolated from kimchi against Escherichia coli and Staphylococcus aureus bacteria. We conducted a Disk Diffusion Method to tests the bacteriocin activity, and data were descriptively analyzed. The results showed that eight isolates of lactic acid bacteria from store-bought kimchi and homemade kimchi homemade were able to inhibit the growth of tested bacteria, S. aureus and E. coli. Isolate D1 isolated from store-bought kimchi has largest inhibitory capability against S. aureus and E. coli; it has 16.00 mm and 17.33 mm inhibitory zone, respectively. Isolate B2 isolated from homemade kimchi has the most significant inhibitory ability against S. aureus and E. coli; it has 16.67 mm and 17.67 mm inhibitory zone, respectively. The lowest ability to form clear zone was found on isolate D2 isolated from homemade kimchi. The inhibitory zone of produce by strain D2 against S. aureus and E. coli were 7.67 mm and 8.67 mm, respectively.